Contemporary issues in bioethics - Beauchamp, Tom L. (Boston : Wadsworth Cengage Learning, 2014)
This edition provides balanced coverage and detailed analysis of key topics in bioethics, including human reproduction; euthanasia and assisted suicide; genetics and genetic testing; the right to health care; organ donation and transplantation; human and animal research; as well as policy and planning for public health threats. With a diverse range of classic and contemporary essays and landmark court cases written by influential scholars and judges, this anthology will help you understand bioethics from a variety of perspectives.
Includes bibliographical references.
Keywords: Medical ethics; Bioethics